2020
DOI: 10.1159/000507881
|View full text |Cite
|
Sign up to set email alerts
|

Association of Ultrapure Citicoline, Homotaurine and Vitamin E in the Management of Normotensive Glaucoma: A Case Report

Abstract: Normal tension glaucoma (NTG) remains a therapeutic challenge for the ophthalmologist since there are no effective therapies as the main therapeutic target, i.e., the intraocular pressure (IOP) increase, is missed. We report on the effectiveness of two neuroprotective molecules (ultrapure citicoline plus homotaurine), in combination with a topical hypotensive approach, in the management of NTG in a long-term follow-up (30 months). A 38-year-old Caucasian woman with no significant medical history and a diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Studies of African American women aged between 65 and 94 demonstrated that oral consumption of fruits and vegetables that contain high levels of vitamins A and C and carotenoids may be associated with reduced risk of glaucoma [75]. Furthermore, a case study reported that an NTG patient who received dietary supplement containing a mixture of citicoline, homotaurine and vitamin E once a day with a topical brimonidine and brinzolamide drops showed a significant improvement in visual field and stable retinal fiber layer and ganglion cells, suggesting a synergic neuroprotective effect from the dietary supplement [76]. On the other hand, a prospective study indicated that a higher dietary intake of vitamins C, E or A had no effect on risks of glaucoma [77,78].…”
Section: Effects Of Dietary Intake Of Antioxidants In Glaucoma Patientsmentioning
confidence: 99%
“…Studies of African American women aged between 65 and 94 demonstrated that oral consumption of fruits and vegetables that contain high levels of vitamins A and C and carotenoids may be associated with reduced risk of glaucoma [75]. Furthermore, a case study reported that an NTG patient who received dietary supplement containing a mixture of citicoline, homotaurine and vitamin E once a day with a topical brimonidine and brinzolamide drops showed a significant improvement in visual field and stable retinal fiber layer and ganglion cells, suggesting a synergic neuroprotective effect from the dietary supplement [76]. On the other hand, a prospective study indicated that a higher dietary intake of vitamins C, E or A had no effect on risks of glaucoma [77,78].…”
Section: Effects Of Dietary Intake Of Antioxidants In Glaucoma Patientsmentioning
confidence: 99%
“…Vitamin E (tocopherol) has an important protective action on cell membranes, protecting them against oxidation by free radicals, it inhibits platelet aggregation and supports cell turnover. [21] The possible synergistic action of these substances administered as a fixed combination could play a role in limiting the apoptosis of the retinal ganglion cells of patients with hypertensive primary open-angle glaucoma (POAG-HT).…”
Section: Introductionmentioning
confidence: 99%